Intrapartum Fetal Heart Rate: A Possible Predictor of Neonatal Acidemia and APGAR Score - Medeiros, Thâmila Kamila de Souza; Dobre, Mirela; da Silva, Daniela Monteiro Baptista; Brateanu, Andrei; Baltatu, Ovidiu Constantin; Campos, Luciana Aparecida (Frontiers in Physiology, 2018)
Background: Predicting perinatal outcomes based on patterns of fetal heart rate (FHR) remains a challenge. The aim of this study was to evaluate intrapartum FHR variability as possible predictor for neonatal acidemia and APGAR score. Methods: This was a cross-sectional study of 552 childbirths. Multivariable linear regression models were used to assess the association between FHR variability and each of the following outcomes: arterial cord blood pH and base deficit, Apgar 1 and 5 scores. Variables used for adjustment were mother age, comorbidities (gestational diabetes, preeclampsia, maternal fever, hypertension), parity, gravidity, uterine contractions, and newborn gestational age and weight at birth. Results: The following factors were associated with an increased risk of metabolic acidosis and low Apgar scores at birth: increased mean and coefficient of variation of the FHR, type of delivery and decreased parity. Each 10-beat/min increase in the FHR was associated with an increase of 0.43 mEq/L in the base deficit, and a decrease of 0.01 in the pH, 0.2 in the Apgar 1 and 0.14 in the Apgar 5 scores. Each 10% increase in the coefficient of variation of the FHR was associated with an increase of 4.05 mEq/L in the base deficit and a decrease of 0.13 in the pH, 1.31 in the Apgar 1 and 0.86 in the Apgar 5 scores. Conclusions: These data suggest the intrapartum FHR variability is physiologically relevant and can be used for predicting the acidemia and Apgar scores at birth.